100-102 Belvidere Street, n.d. - Unknown (Tufts Archival Research Center, 2005)
Street-level view of (left to right) 100-102 Belvidere Street, located between Falmouth Street to the east and Dalton Street to the west. Parking meters line the sidewalk in front of the dwellings. 8 x 7 1/2, 10 x 8 overall Photographs